Characteristics of measles keratoconjunctivitis in adults (Ukrainian Journal of Ophthalmology, 2026)
Introduction.  Measles (lat. morbilli) is an acute anthroponotic infectious virus disease with a high contagion level. In general, measles is common for children. However, there are a good number of the diseased among adults. A clinical picture of measles in adults is characterized by more intensive symptoms and by more likely development of complications.Purpose. To analyze the clinical course of measles keratoconjunctivitis in adults.Materials and Methods. In 2017, we followed up two patients (aged 34 and 42) having had measles with an atypical disease course. Both patients were diagnosed bilateral conjunctivitis and superficial punctate keratitis. Dry eye syndrome was moderate. The patients were performed anti-inflammatory, antiviral, desensitizing and substitutional therapy. 3 days after treatment onset, the patients' complaints decreased and biomicroscopy findings were improved. At Day 7, the subjective complaints and clinical signs almost disappeared.Conclusion. The course of measles in adults is of particular severity. Measles keratoconjunctivitis is characterized by punctuate eruption in the cornea and pronounced dry eye syndrome. Early therapy enabled to regress the process and to recover the vision within a short period of time.
Keywords: keratitis; measles; keratoconjunctivitis; epitheliopathy